Pelatihan Kader Sebaya Anti Narkoba untuk Pencegahan HIV/AIDS di Pondok Pesantren Manarul Huda - Alin Layinatunnisa; Teni Andriani; Intan Monica; Yova Syahril Maulana; Rizal Darojatun Iman; Gilang Ramadhan; Amnah Rizkiyani (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Introduction: In addition to being experts in moral and spiritual development, it is hoped that students and boarding school administrators are experts in health development and can become motivators and innovators in improving health status. Having a varied culture because it comes from various regions in Indonesia, is one of the risk factors for smoking behavior which is the entry point for drug abuse. Health problems such as scabies, malnutrition, homosexuality and the risk of contracting HIV/AIDS are often found among students and still need attention. Objective: To determine the effectiveness of counseling and training of anti-drug peer cadres to prevent the transmission or spread of HIV/AIDS in Islamic boarding schools. It is hoped that after the implementation of this community service, the students can become peer cadres who are able to think, be responsible, behave and act positively. Method: This activity was carried out using lecture and question and answer methods as well as leaflet print media. opened with an introductory greeting, conveying the goals, objectives and contracts for community service. Before discussing the material, it is necessary to explore the knowledge of the students. Result: After being given counseling, 92.8% of participants understood that they were able to explain again about the causes, principles and modes of transmission of HIV/AIDS during the evaluation. Then 7.2% still do not fully understand the material presented. These results indicate that there is an increase in knowledge and a change in views towards PLWHA. Conclussion: The implementation of the community service activity “Training Peer Cardes Anti-Drugs at the Manarul Huda Ciamis Boarding School” has been carried out and been well received. In practice, the participants gave a positive response by listening to the explanations of the presenters and actively asking questions about the material presented.